Paliativna oskrba v Sloveniji in izzivi za prihodnost - Lunder, Urška (Zdravniški vestnik, 2003)
Background. Palliative care in Slovene health care system isn't developed. Comparison with other countries is not possible in many aspects. There is no complete or appropriately educated palliative care team in hospitals or in primary care. Palliative care departments in hospitals and nursing homes do not exist. Holistic palliative home care is offered only by Slovene association of hospice. The pressure on nursing homes and nursing service departments isgetting stronger Standards and norms for staff, for living conditions and medical equipment do not allow any more admittances of patientswith the needs of high category of care in these institutions. Conclusions. Indirect indicators of level ofpalliative care (e.g. morphine consumption, palliative care departments, home care network, undergraduate education, specialisation and research) put Slovenia at the bade of the Europe. Statistics predict aging of population and more patients are also living with consequences of progressive chronic diseases and cancer. In the new healthcare reform there is an opportunity for palliative care to getan equalplace in healthcare system. With coordiriated implementation of palliative care departments, consultant teams and mobile specialistic teams, palliative care could reach a better level of quality. At the same time, quality permanent education is essential.
Keywords: Domovi za starostnike; Homes For The Aged; Hospitalizacija; Hospitalization; Morfijevi derivati; Morphine Derivatives; Mortality; organizacija zdravstva; Paliativna oskrba; Palliative Care; Slovenia; Slovenija; Therapeutic Use; Umrljivost